Handling Load intensive Applications Using Aneka Cloud Platform Integrated with Amazon EC2 - Manjula, K.; Sundaram, S. Meenakshi (Current Topics on Mathematics and Computer Science Vol. 4, 2021)
Performance of the distributed network can be evaluated based on the parameters such as response time and throughput. Computing nodes in the local distributed network will have its own limitation in terms of storage, computing capacity and resource availability which will degrade the performance of the network. The local distributed network will serve the minimum number of user requests. With the advent of internet and growing capacity of technology, the number of users accessing the network is increasing tremendously and the requirements of the users is also varying dynamically. Thus in this research paper, thread model based application is run on private cloud with 10 worker machines with varying number of tasks and the same number of tasks has been taken and run on the hybrid cloud enabling dynamic provisioning extending the resources of the private cloud to meet Quality of Service, to handle the dynamic changes in the user load on the distributed network using Amazon EC2 provisioning and resource management configuration.